2022
DOI: 10.7759/cureus.25897
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Assessment of the Temporomandibular Joint Changes Following Reversed Twin Block Therapy of Patients With Skeletal Class III Malocclusion in Conjunction With the Photobiomodulation Therapy: A Randomized Controlled Clinical Trial

Abstract: Background: Despite the positive effect of the photobiomodulation therapy (PBMT) application on animals, the primary role of this technique on the human condyle is still unclear. Several experimental reports have shown the efficacy of PBMT in inducing cellular changes in the temporomandibular joint (TMJ) region during functional treatment of patients with skeletal deformities. Still, the lack of information about its effects on human condyles requires further studies. Objectives: This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 45 publications
0
11
0
14
Order By: Relevance
“…La MCA fue evaluada por un over jet negativo (< 0 mm) 9 , 27 o de -1,7 mm, 25 mordida borde a borde 8 , 24 y consideraron el overjet negativo que comprometieran tres a cuatro dientes antero inferiores sobre los dientes antero superiores. 2 , 8 , 22 , 23 , 24 Algunos estudios incluyeron el prognatismo mandibular, (19.24) retrognatismo maxilar, 8 , 22 , 23 patrón de crecimiento horizontal 8 , 9 y relación molar Clase III según Angle 9 , 19 , 27 o Superclase I 9 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…La MCA fue evaluada por un over jet negativo (< 0 mm) 9 , 27 o de -1,7 mm, 25 mordida borde a borde 8 , 24 y consideraron el overjet negativo que comprometieran tres a cuatro dientes antero inferiores sobre los dientes antero superiores. 2 , 8 , 22 , 23 , 24 Algunos estudios incluyeron el prognatismo mandibular, (19.24) retrognatismo maxilar, 8 , 22 , 23 patrón de crecimiento horizontal 8 , 9 y relación molar Clase III según Angle 9 , 19 , 27 o Superclase I 9 .…”
Section: Resultsunclassified
“…Tres estudios analizaron la presencia de cambios en el ATM, el aparato funcional evaluado fue el twin block reverso (TBR) 2 , 19 y el jasper jumper modificado (JJM) 8 . La cantidad de pacientes en el TBR estudiado oscilaba de 20 a 32.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Khwanda et al [ 34 ] evaluated the effect of photobiomodulation therapy (PBMT) on the TMJ components following class III treatment with the reversed twin block (RTB) appliance in growing patients. Their results indicated that condylar volume was significantly increased in the RTB group only by a mean of 287.97 mm cube.…”
Section: Reviewmentioning
confidence: 99%
“…Their results indicated that condylar volume was significantly increased in the RTB group only by a mean of 287.97 mm cube. There were no considerable differences in the condylar position after the class III treatment between the RTB and RTB+PBMT groups [ 34 ].…”
Section: Reviewmentioning
confidence: 99%